2024
DOI: 10.3390/ijms25052518
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profile and Antioxidant and Antimicrobial Activity of Rosa canina L. Dried Fruit Commercially Available in Serbia

Vojkan M. Miljković,
Ljubiša Nikolić,
Jelena Mrmošanin
et al.

Abstract: The aim of this work was to give as much information as possible on Rosa canina dried fruit that is commercially available in Serbia. In order to provide the chemical composition, the UHPLC-DAD-ESI-MS method was employed for both polar and non-polar extracts of samples obtained with a solvent mixture consisting of hexane, acetone, and ethanol in a volume ratio of 2:1:1, respectively, and 0.05% (w/v) butylated hydroxytoluene. In addition, the total content levels of lycopene, β-carotene, total polyphenols, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…In addition to their antimicrobial properties, medicinal plants have long been regarded as a traditional source of antifungal remedies [ 75 ]. Many studies demonstrated antifungal activities of Caucasian medicinal plants against different fungal species, including Candida [ 25 , 29 , 36 , 39 , 41 , 46 , 47 , 49 , 50 , 54 , 56 , 63 , 66 ]. Significant activity against the Candida species was revealed for the essential oil obtained from the aerial parts of Clinopodium nepeta (L.) Kuntze [ 43 ] and the acetone extracts of A. eupatoria plants [ 36 ], as well as the methanol extracts of P. harmala [ 66 ] and the essential oil obtained from the flowering aerial parts of M. pulegium [ 46 ].…”
Section: Antimicrobial and Antifungal Activity Of Caucasian Medicinal...mentioning
confidence: 99%
“…In addition to their antimicrobial properties, medicinal plants have long been regarded as a traditional source of antifungal remedies [ 75 ]. Many studies demonstrated antifungal activities of Caucasian medicinal plants against different fungal species, including Candida [ 25 , 29 , 36 , 39 , 41 , 46 , 47 , 49 , 50 , 54 , 56 , 63 , 66 ]. Significant activity against the Candida species was revealed for the essential oil obtained from the aerial parts of Clinopodium nepeta (L.) Kuntze [ 43 ] and the acetone extracts of A. eupatoria plants [ 36 ], as well as the methanol extracts of P. harmala [ 66 ] and the essential oil obtained from the flowering aerial parts of M. pulegium [ 46 ].…”
Section: Antimicrobial and Antifungal Activity Of Caucasian Medicinal...mentioning
confidence: 99%